Nilai Pendidikan Moral dalam Film 172 Days: Analisis Wacana Kritis Teun A. Van Dijk - Nurhikmah, Nurhikmah; Sumiyati, Sumiyati; Sukrisno, Sukrisno; Dewi, Hepta Pracipta; Charlina, Charlina (Medan Resource Center, 2023)
Films wield significant societal influence by imparting moral messages, particularly resonating with the millennial demographic. This study delves into the moral narrative of the true-story-based film